"Waiting for the Barbarians": Identity and Polemicism in the Neo-Patristic Synthesis of Georges Florovsky - Gallaher, Brandon (Modern theology, 2011)
Georges Florovsky (1893-1979), with his "neo-patristic synthesis", is perhaps the most influential modern Orthodox theologian, having mentored and/or taught such theologians as Lossky and Zizioulas. However, his theology enshrines a troubling paradigm where a Pan-Orthodox Eastern identity ("Christian Hellenism") is asserted over against the heterodoxy of an Other which is often the West. The article traces this paradigm then argues that Florovsky's construction of Eastern Orthodoxy is dependent on German Romanticism and that his polemicism blinded him to this fact. It briefly suggests, on the basis of the Chalcedonian definition, a new 'dialectical' theology of ecclesial identity where identity is established in an encounter with the Other, rather than in demonizing it.